Increasing Knowledge Of Analytical Chemistry Subjects Through Intensive Counseling On Student That Has Background IPS Prodi DIII Nutrition Poltekkes Kemenkes Semarang - Suharni Iriyanti; Soesanto Soesanto; Surati Surati (Jurnal LINK, 2013)
Analytical chemistry subjects is a scientific subjects and skills. Analytical chemistry subjects in the extension class consisting of 44 students turned out 15 people do not pass the exam on the final test of semester 1. After traced, apparently ± 88% comes from Senior High School (SMU) Social Studies Department (IPS). It is caused Senior High School students social studies department does not have a sufficient basis on chemical subjects, it takes special treatment to improve student’s ability to understand the background subjects Chemistry, for example, analytical chemistry, food chemistry, Biochemistry, Food Technology and Food Quality Supervision and other. Research purposes : fixes the value of analytical chemistry subjects by increasing student motivation to learn, by giving the task at the end of each lecture to students with the aim of students want to repeat subject at home, calculate the average value of pre test, calculate the average value of post test and calculate the absorption of regular classes A and B. This research is classroom action research which will be implemented to the first semester students regular classes Prodi DIII Nutrition Poltekkes Depkes Semarang began the first semester 2009/2010 until the end of semester exams (8 meetings). Outline analytical chemistry courses are chemicals (solid, liquid and gas) risk and countermeasures of chemicals, qualitative and quantitative equipments, standardization, asidialkalimetri, permanganometri, yodometri and yodimetri, argentometry and the application. to support the analytical chemistry subjects required understanding, intensive guidance, motivation to learn, pre test, post test, questions and answers and assignments. The average value of pre-test and post-test (mean, median, minimum and standard deviation values) an increase in the value of pre-test to post-test is equal to 36.01%. As well as for absorption the middle test scores (UTS) to the final test scores (UAS) up to 18,75% for regular classes A and regular classes B up to 18,89%.